2012
DOI: 10.1186/1756-3305-5-169
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of Renylaima capensis, a brachylaimid trematode of shrews and slugs in South Africa: two-host and three-host transmission modalities suggested by epizootiology and DNA sequencing

Abstract: BackgroundThe life cycle of the brachylaimid trematode species Renylaima capensis, infecting the urinary system of the shrew Myosorex varius (Mammalia: Soricidae: Crocidosoricinae) in the Hottentots Holland Nature Reserve, South Africa, has been elucidated by a study of its larval stages, epizootiological data in local snails and mammals during a 34-year period, and its verification with mtDNA sequencing.MethodsParasites obtained from dissected animals were mounted in microscope slides for the parasitological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…One interesting fi nding in this study was the recovery of the metacercariae of a brachylaimid trematode from the rectum of H. galamensis. Members of the Brachylaimidae are parasitic mostly in domestic and wild birds as well as in some small mammals (Alicata, 1940;Ulmer, 1951a, b;Sirgel et al, 2012) and use terrestrial gastropods as fi rst and second intermediate hosts. The only brachylaimid trematode known so far to have an amphibian defi nitive host is Zeylanurotrema spearei, which is parasitic in the urinary bladder of Bufo marinus (see Cribb and Barton, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting fi nding in this study was the recovery of the metacercariae of a brachylaimid trematode from the rectum of H. galamensis. Members of the Brachylaimidae are parasitic mostly in domestic and wild birds as well as in some small mammals (Alicata, 1940;Ulmer, 1951a, b;Sirgel et al, 2012) and use terrestrial gastropods as fi rst and second intermediate hosts. The only brachylaimid trematode known so far to have an amphibian defi nitive host is Zeylanurotrema spearei, which is parasitic in the urinary bladder of Bufo marinus (see Cribb and Barton, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships of brachylaimids were inferred by sequences of 28S rDNA and cox1, using an unknown species found in this study and related taxa published in DNA databases [29,30,31,32]. The NJ phylogenetic trees of the two genes strongly suggested that the unknown species belongs to the genus Brachylaima, although the number of taxa available for the tree construction was insufficient ( Supplementary Fig.…”
Section: Dna Phylogeny and Diversitymentioning
confidence: 99%
“…worldwide (Thiengo and Amato, 1995;Barger and Hnida, 2008;Barger, 2011;Sirgel et al, 2012;Valente et al, 2016;Gracenea and Gállego, 2017;Nakao et al, 2017), only sporocysts and cercariae have been reported in Helix aspersa as a first intermediate host in Turkey (Köse et al, 2015); metacercariae have not been reported.…”
mentioning
confidence: 99%
“…Land snails and slugs are required as the first and second intermediate hosts in the life cycle of Brachylaima spp. (Yamaguti, 1975;Butcher and Grove, 2005;Barger and Hnida, 2008;Barger, 2011;Sirgel et al, 2012;Valente et al, 2016). First intermediate hosts have sporocysts and cercariae, and second intermediate hosts have metacercariae of Brachylaima spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation